Javanese Traditional Culture “Temu Manten”: Part of Javanese Acculturation Society in Sumatera - Naila Rohmaniyah; Mohammad Syawaludin; Abdullah Idi; Agus Sholikhin (JUSPI (Jurnal Sejarah Peradaban Islam), 2023)
This reseach aims to describe the acculturation of the Javanese traditional culture wich name is “Temu Manten. This is the cultural root of the Javanese people that has occurred in all parts of Sumatra, especially South Sumatra. Researcher used qualitative research, it is descriptive type by Schutz's phenomenological theory research approach. The researcher describes a symptom, fact, event and problem. The researcher used two primary data sources (observations and interviews) and secondary (the results of research, books and other sources as other data sources). The researcher took purposive sampling to determine the informants. Analytical descriptive is used by researcher to describe their findings. As the results of this study found that the acculturation of the Javanese traditional culture which called as “Temu Manten” does not only occur in South Sumatra, but has occurred in various regions on the island of Sumatra. The factors that influenced the acculturation of this culture are the existence of transmigration, migration, inter-ethnic marriage, level of education, modernization and globalization. However, cultural acculturation in Indonesia got rich in culture that can be preserved to remain and known by next generations of Indonesia.